2008
DOI: 10.1534/genetics.108.092379
|View full text |Cite
|
Sign up to set email alerts
|

Muller's Ratchet and the Degeneration of Y Chromosomes: A Simulation Study

Abstract: A typical pattern in sex chromosome evolution is that Y chromosomes are small and have lost many of their genes. One mechanism that might explain the degeneration of Y chromosomes is Muller's ratchet, the perpetual stochastic loss of linkage groups carrying the fewest number of deleterious mutations. This process has been investigated theoretically mainly for asexual, haploid populations. Here, I construct a model of a sexual population where deleterious mutations arise on both X and Y chromosomes. Simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…The heterochromatic and gene-poor nature of the Y chromosome is consistent with theoretical models that predict rapid degeneration and specialization for male-specific functions of Y chromosomes in the absence of recombination (7)(8)(9). Furthermore, the hemizygous nature of the Y chromosome, combined with the lack of recombination, makes it uniquely susceptible to population genetic processes that reduce genetic variation and limit adaptation (10)(11)(12)(13).…”
supporting
confidence: 75%
“…The heterochromatic and gene-poor nature of the Y chromosome is consistent with theoretical models that predict rapid degeneration and specialization for male-specific functions of Y chromosomes in the absence of recombination (7)(8)(9). Furthermore, the hemizygous nature of the Y chromosome, combined with the lack of recombination, makes it uniquely susceptible to population genetic processes that reduce genetic variation and limit adaptation (10)(11)(12)(13).…”
supporting
confidence: 75%
“…In addition, Engelstädter (2008) showed that, in some circumstances, the presence of low-frequency deleterious mutations on X-linked homologs of the Y chromosome can greatly slow down the ratchet, compared with what is found in haploid simulations of the type used here.…”
Section: Plausibility Of the Modelmentioning
confidence: 59%
“…When U ¼ 1.89, the ratchet was stalled for short chromosomes (L ¼ 32 kb), but was going at a relative rate of 0.4% for L ¼ 1.28 Mb. As previously suggested (Bachtrog 2008b;Engelstädter 2008), the speed of the ratchet is likely to vary over different stages of Y chromosome degeneration: when the overall occurrence of major mutations is still high, interference among very strongly selected mutations alone leads to their fast accumulation, and the process is accelerated (about two-to fourfold) by the presence of BGS sites. With the erosion of genes from the neo-Y, U decreases and the ratchet slows down, but the effect of mutations at nonsynonymous sites starts to increase, until U becomes so low that the BGS effect cannot greatly increase the ratchet any longer (eventually the BGS effect will disappear as well).…”
Section: Discussionmentioning
confidence: 83%
“…First, to the extent that gene duplicates are fixed via positive selection, they are less likely to become fixed on nonrecombining relative to recombining chromosomes (Otto and Goldstein 1992;Clark 1994;Yong 1998;Otto and Yong 2002;Tanaka and Takahasi 2009). Second, regardless of whether Y-linked duplicates become fixed via genetic drift or by natural selection, the actions of Muller's ratchet, genetic hitchhiking, and background selection are expected to greatly increase the probability that Y-linked genes degenerate into nonfunctional pseudogenes Bachtrog 2006;Engelstadter 2008).…”
mentioning
confidence: 99%